Performance measures of marketing efforts in the manufacturing and service industries (retailing and banking) - Lam, Ruoh Wei (2015)
The purpose of this research is to let the reader gain a better understanding of performance measures of marketing efforts in the manufacturing and service industries, specifically the retailing and banking industries. Though marketing has evolved to become an increasingly important factor to survival in the highly competitive business environment, there is little literature written on the ways to enhance its effectiveness. As a result, this study chose to probe deeper into the performance measures of the marketing efforts that the 3 industries engaged in. Due to the lack of up-to-date information on performance measures, the group did a survey to investigate this particular aspect of marketing. Out of 150 questionnaires that were sent out to 50 companies in each respective industry, the group received 21 responses which amounted to a 14% response rate. This is acceptable as compared to the general response rate of 10% experienced in Singapore. An analysis of the data and questionnaire is included to further discuss and review the norms and practices of the 3 industries, with respect to their marketing efforts.